Analisis Kebutuhan Model Media Audio Cerita Wayang Bagi Remaja - Mariana Susanti; Sri Wahyuni (Jurnal Pekommas, 2017)
Puppet was the cultural heritage of Indonesia and a world heritage whose many advantages and some disadvantages. Indonesian youth was considered away from the puppet. Unit of Educational and Culture of Radio Media Development addressed this phenomenon by conducting a needs analysis of puppet stories as audio media character education for the younger generation, in particular adolescent ages 12-18 years. The analysis was conducted to uncover the adolescent perception about the puppet and how their need about the puppet which was broadcasted through the radio. This study used the survey method and involved radio stations in Middle Java and Eastern Java, which had been partnered with BPMRPK and had founded school and student community. The results showed that teens are considered the main attractive of the puppet performances was at the story. Teens considered puppet stories would be interesting if the radio broadcast program was made by adjusting the present context. Most teens need a puppet story radio broadcast in the form of a recording, duration of 30 minutes, and aired every day.Wayang merupakan warisan budaya Nusantara sekaligus warisan budaya dunia yang memiliki banyak kelebihan dan kekurangan. Sekarang ini generasi muda Indonesia dianggap tidak lagi memerhatikan keberadaan wayang. Balai Pengembangan Media Radio Pendidikan dan Kebudayaan (BPMRPK) menyikapi fenomena ini dengan melakukan analisis kebutuhan tentang cerita wayang sebagai media audio pendidikan karakter bagi generasi muda, khususnya remaja usia 12-18 tahun. Analisis dilakukan untuk mengungkap pandangan remaja tentang kesenian wayang dan bagaimana kebutuhan remaja tentang kesenian wayang yang disiarkan melalui media radio. Penelitian ini menggunakan metode survei dengan melibatkan stasiun radio mitra di Jawa Tengah dan Jawa Timur yang memiliki sekolah binaan atau komunitas pelajar. Hasil penelitian menunjukkan bahwa remaja menganggap daya tarik utama pertunjukan wayang adalah pada cerita. Remaja menganggap cerita wayang akan menarik bila dijadikan program siaran radio dengan menyesuaikan konteks masa kini. Sebagian remaja membutuhkan siaran radio cerita wayang dalam bentuk rekaman yang berdurasi 30 menit dan disiarkan setiap hari.